THE ROLE AND SCOPE OF THE GENERAL URBAN PLAN IN CONTEMPORARY PLANNING IN BELGRADE - Graovac, Ana; Đokić, Jasmina; Teofilović, Anica; Teofilović, Vesna (Arhitektura i urbanizam, 2021)
This paper investigates the General urban plan (GUP), as a traditional planning instrument that can respond to the challenges of the contemporary social context. Given that in 2019 a decision was made to develop a new GUP of Belgrade, which should offer a strategic spatial and urban solution based on the principles of social, economic, environmental and cultural sustainability to be developed in the coming decades, the question is what is and what should be the GUP and what should it look like, but perhaps most importantly - what can be included in the GUP be today? The role and scope of the General urban plan are explored from two aspects. In the first, the role of the GUP is analyzed within the institutional framework - the Law on planning and construction and the Law on the planning system of the RS, which was adopted in 2018, as well as their connection, interaction and the possibilities that arise from it. In the second step, the scope of the GUP is explored through an assessment of contemporary planning practice in Belgrade, with the General plan of Belgrade 2021 adopted in 2003 as its cornerstone, and then analyzing the changes in planning that occurred through its further implementation and detailed elaboration. While the strategic role of the GUP is increasing with the possibility of connecting both planning systems, in practice its importance and scope are continuously weakening, leaving the planned growth and development of Belgrade to the economic interests related to individual locations.